Lattice site location and optical activity of Er implanted ZnO - Alves, E.
ZnO (O face) single crystals were implanted with 150 keV Er+ ions to fluences of 5 × 1014 and 5 × 1015 Er+/cm2 at room temperature. For fluences of 5 × 1015 Er+/cm2 the implantation damage raises the minimum yield from 2% to 22%. Despite the large amount of damage a fraction of 90% of the implanted Er ions are incorporated in substitutional sites along the [0 0 0 1] axis. Photoluminescence (PL) studies reveal the presence of a weak emission near 1.54 μm at 77 K due to the 4I13/2→4I15/2 transition of the Er3+ ions. Annealing in oxidizing atmosphere at 800 °C leads to a reduction of the implantation damage, which is fully recovered after annealing at 1050 °C for 30 min. The annealing at 1050 °C leads to the outdiffusion of Er, with a 50% loss from the implanted region after the annealing. Only a fraction of 25% of the remaining Er is still in regular sites after the annealing and the Er3+ PL vanishes